Regional Financial Management Accountability in the Perspective of Public Sector Accounting - Yuniati Yuniati; Yuni Oktaviani; Zahra Hardyanti; Wandy Zulkarnaen (Universitas Dharma Wacana, 2026)
To ensure transparency, efficiency, and accountability in the use of public funds, accountability in regional financial management is needed, which is one of the two main foundations in public sector accounting practice. In addition, the demands of the community with a government that is run in a clean and accountable manner have increased the government's need to improve the quality of financial management. The government improves the quality of financial management through the implementation of government accounting standards and an adequate internal control system. Therefore, this study aims to examine the accountability of regional financial management from the perspective of public sector accounting through a literature study approach. The method used in this study is a literature study of accredited national journals in the last five years, textbooks, and relevant laws and regulations. The results of this study show that the role, the government's internal control system, the quality of human resources, and the use of Government Accounting Standards, and the role of internal & external supervision have a significant influence on improving the level of accountability of regional financial management. However, there are still a number of structural and technical obstacles that still have the potential to be stumbling blocks to the realization of optimal accountability. Therefore, there is a need for a commitment by the government to improve financial governance that allows each public entity to be more accountable and open.